Daya Antibakteri Gum Arabic Baluran terhadap Pertumbuhan Aggregatibacter actinomycetemcomitas - Dina Berliana Wulandari (Fakultas Kedokteran Gigi, 2025)
Introduction: Periodontitis is an inflammatory disease caused by infection of the periodontal tissue due to the presence of pathogenic bacteria, one of which is Aggregatibacter actinomycetemcomitans. Periodontitis treatment includes scaling, root planning and supportive therapy using chlorhexidine. Long-term use of chlorhexidine causes side effects for oral health so it is necessary to find alternatives with minimal side effects. Gum Arabic Baluran contains active ingredients as antibacterials including polyphenols, tannins, flavonoids, saponins and terpenoids. This study aims to determine the antibacterial power of Baluran Arabic Gum at concentrations of 12.5 mg/ml, 25 mg/ml, 50 mg/ml, 100 mg/ml on the growth of A. actinomycetemcomitans and to determine the greatest concentration in inhibiting A. actinomycetemcomitans. Method: Gum Arabic extracts concentrations 12,5 mg/ml, 25 mg/ml, 50 mg/ml, and 100 mg/ml were made by extracting Gum Arabic using the sonication method. Antibacterial activity test was conducted using disc diffusion method on MHA media that had been inoculated with A. actinomycetemcomitans then measured the diameter of the inhibition zone formed around the disc paper. Results: there was an inhibition zone at concentrations of 25 mg/ml, 50 mg/ml, 100 mg/ml and no inhibition zone was formed at a concentration of 12.5 mg/ml. The lowest inhibition zone was formed in Gum Arabic extract with a concentration of 12.5 mg/ml, namely with an inhibition zone diameter of 0 mm. While the highest inhibition zone was formed at a concentration of 100 mg/ml with an average inhibition zone of 14.80 mg/ml. Conclusion: Baluran Gum Arabic extract with concentrations of 25 mg/ml, 50 mg/ml and 100 mg/ml has antibacterial activity to inhibit the growth of A. actinomycetemcomitans and a concentration of 100 mg/ml is the highest concentration in inhibiting growth of A. actinomycetemcomitans.
Reaploud Repository February_Hasyim
Keywords: Gum Arabic; Aggregatibacter actinomycetemcomitans; antibacterial